"Learning Interest Index": An Inventory Test for Assessing Learning Motivation in Adolescents - Tolstykh N.N; Fyodorov V.V; Kharchenko M.A; Pogodina A.V; Babanin P.A (Moscow State University of Psychology and Education, 2021)
The article provides theoretical justification and describes the development, psychometric verification and approbation of the Learning Interest Index inventory for assessing learning motivation in adolescents of different age groups. The theoretical basis was a resource approach aimed at identifying those motivational-value and personality components that make a significant positive contribution to both the process and the result of learning activities of adolescents. The sample for psychometric verification of the test consisted of 572 adolescents (44.5% boys, 55.5% girls) studying in 7-11 grades of several medium-ranked schools of Moscow and the Moscow region. To identify the structure of learning interest, exploratory factor analysis was applied separately for the sub-samples of middle (grades 7-9) and older (grades 10-11) adolescents. The model of the Learning Interest Index includes both simple, unambiguous, and complex, combined factors. For a sample of middle-aged adolescents, a seven-factor model of the Learning Interest Index was obtained. The structure of the learning interest of older adolescents includes nine factors. Psychometric verification showed that all scales of the questionnaire have acceptable reliability, as well as construct and empirical validity.